2016
DOI: 10.18632/oncotarget.14361
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA network analysis identifies critical genes among the different breast cancer subtypes

Abstract: Although competing endogenous RNAs (ceRNAs) have been implicated in many solid tumors, their roles in breast cancer subtypes are not well understood. We therefore generated a ceRNA network for each subtype based on the significance of both, positive co-expression and the shared miRNAs, in the corresponding subtype miRNA dys-regulatory network, which was constructed based on negative regulations between differentially expressed miRNAs and targets. All four subtype ceRNA networks exhibited scale-free architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…In recent years, some studies have investigated the ceRNAs in BC. For instance, Chen et al [ 32 ] analyzed the BC ceRNA network on the basis of common miRNAs as well as co-expression, but did not consider miRNA expression. Another study also established a BC specific ceRNA network to investigate its underlying molecular mechanisms based on the PCC of miRNA–mRNA pairs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have investigated the ceRNAs in BC. For instance, Chen et al [ 32 ] analyzed the BC ceRNA network on the basis of common miRNAs as well as co-expression, but did not consider miRNA expression. Another study also established a BC specific ceRNA network to investigate its underlying molecular mechanisms based on the PCC of miRNA–mRNA pairs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had shown that the ERK1/2 activation usually protected neurons from apoptosis, whereas prolonged activation of P38 and/or JNK often caused death [59]. Moreover, Chen reported that P27 expression level Figure 11: Proposed network of ciR8073-miR181a-NTS in the endometrium of dairy goats.…”
Section: Nts Promoted Eecs Proliferation and Inhibited Apoptosis In Vmentioning
confidence: 99%
“…Many studies have illustrated that lncRNAs often combined with the target miRNAs to regulate the expression of mRNAs [ 44 , 45 ]. To measure the potential tumorigenic role of lncRNAs through miR-mediated interaction in BRCA, we used DEGs and DELs to construct a background network and regarded the four groups mentioned above as seeds to mine four sub lncRNA-mRNA ceRNA networks: high-up network, high-down network, low-up network and low-down network (Table 2 and Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%